2018
DOI: 10.1167/18.4.13
|View full text |Cite
|
Sign up to set email alerts
|

Perceptual integration of kinematic components in the recognition of emotional facial expressions

Abstract: According to a long-standing hypothesis in motor control, complex body motion is organized in terms of movement primitives, reducing massively the dimensionality of the underlying control problems. For body movements, this low-dimensional organization has been convincingly demonstrated by the learning of low-dimensional representations from kinematic and EMG data. In contrast, the effective dimensionality of dynamic facial expressions is unknown, and dominant analysis approaches have been based on heuristicall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 63 publications
0
9
0
Order By: Relevance
“…In an experiment similar to ours, it has been shown that hierarchical Gaussian process dynamical models can synthesize hand shake movements indistinguishable from natural ones (Taubert et al 2012). Furthermore, the perception of emotion based on spatio-temporal MPs has been investigated by Roether et al (2009) and Chiovetto et al (2018). In our study, we are interested in comparing different MP types in a unified Bayesian framework (Endres et al 2013) with respect to the perception of naturalness.…”
Section: Related Workmentioning
confidence: 84%
“…In an experiment similar to ours, it has been shown that hierarchical Gaussian process dynamical models can synthesize hand shake movements indistinguishable from natural ones (Taubert et al 2012). Furthermore, the perception of emotion based on spatio-temporal MPs has been investigated by Roether et al (2009) and Chiovetto et al (2018). In our study, we are interested in comparing different MP types in a unified Bayesian framework (Endres et al 2013) with respect to the perception of naturalness.…”
Section: Related Workmentioning
confidence: 84%
“…How many dimensions are used to encode the full space of facial motions, and what are these dimensions? Recent evidence suggests that a small number of dimensions are sufficient (Dobs et al, 2014 ; Chiovetto et al, 2018 ) but more studies based on larger data sets are needed. If a set of basic components can be characterized, can we identify behavioral and neural correlates of a facial motion space, similar to what is known as face space for static faces (Valentine, 2001 ; Leopold et al, 2006 ; Chang and Tsao, 2017 )?…”
Section: Discussionmentioning
confidence: 99%
“…While this previous work focused on the perception of naturalness of movements, the current study addresses the predictive mechanism inherent in MP models. Similar studies were also conducted for MP models of emotional handshakes [Taubert et al 2012] and facial expressions [Chiovetto et al 2018].…”
Section: Related Workmentioning
confidence: 82%